Short run performance of initial public offerings in Nepal - Paudel, Sujan Raj (Journal of Nepalese Management Academia, 2023)
This paper examines the under-pricing and performance of IPO for six months period using the model of under-pricing. Overall, 67 samples are analyzed out of 120 population identified from the period of 2014/15 to November 2020/21 using judgmental sampling and removal of outlying observations. Firm size, subscription rate, issue size, age of firm, issue manager reputation and market condition are taken as independent variables. Nepalese investors mainly prefer microfinance sector for investment and tends to be underpriced for longer period due to high demand for share. Observations are classified into two categories based on mean value of each predicting variable and NEPSE index. Significant difference on initial as well as monthly return has been observed between categories of subscription rate (high versus low) and age (matured versus young). Highly positive and significant correlation between the issue size and firm size shows large firm issue IPO in large size and negative significant correlation between issue size and subscription rate shows when issue size is low there will be high demand for shares. Significant relationship of subscription rate and age of firm for initial and first month return has been observed whereas only subscription rate was found significant after second month to sixth month. Study concludes that subscription rate is major determinant of under-pricing of IPOs in the Nepalese Stock Market.